Wykluczenie bonum prolis w opublikowanych wyrokach Roty Rzymskiej z 2002 r. - Góralski, Wojciech (Ius Matrimoniale, 2013)
Bonum prolis, constituting one of three goods of Saint Augustine, including procreation and bringing up children, connected integrally with bonum coniugum, has been the subject of simulation (so called partial simulation) of the marital consensus, i.e. exclusion – the positive act of will – right to fulfill marital acts aiming per se at procreation. Based on the analysis of five published judgments of the Roman Rota issued in 2002 the author presents the meaning of bonum prolis for the marital unity and the exclusion of this good (with respect to the procreation), differentiates the exclusion of the right to procreation itself from the exclusion of exercising this law only, takes into consideration the concurrence of bonum prolis exclusion with bonum sacramenti exclusion, and, finally, discusses proofs for the bonum prolis exclusion. The analysis of the judgments is preceded by presenting the issue of the procreative meaning of the marriage and the effectiveness nullifying the marital consensus arising from the intention contrary to the procreation.